La prolongation de la durée d'un dépôt, à travers l'expérience du Calvados - Bernard, Gildas (Gazette des archives, 1980)

Les éliminations - Burckard, François (Gazette des archives, 1980)
Archive Disposal. This question was debated by the Association des Archivistes français in 1979. The problem presents itself on différent terms from one département to another, and from National archives to local archives. The needs of research, either present or future, are difficult to evaluate. Computer-produced records are one of the main causes of overstockage. Elaboration and diffusion of disposal schedules or selection rules is the most generally recommended solution.

L'interdépendance des archives et de la gestion de documents : une approche globale et archivistique - Ducharme, Jacques (Archives, 1980)

Pré-archivage ou gestion de documents ? Le problème de la terminologie des archives administratives - Pepermans, Raymond (L'actualité terminologique, 1980)